The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1590/1806-9282.20210997
|View full text |Cite
|
Sign up to set email alerts
|

Blood count and fasting blood glucose level in the assessment of prognosis and survival in advanced cervical cancer

Abstract: OBJECTIVE:The objective of this study was to verify whether the parameters of the blood count and the fasting glucose level before treatment are related to prognosis and survival in cervical cancer (IIB-IVB staging). METHODS: Patients with cervical cancer (stages IIB-IVB) were evaluated (n=80). Age, parity, staging, histological grade, histological type, hemoglobin, red blood cells, hematocrit, neutrophil, lymphocyte and platelet counts, red blood cell distribution width, neutrophil-lymphocyte ratio, plateletl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…In our study, we also evaluated other pertinent markers, including ALB, AGR, total protein, Hb, and BMI, which have previously been reported as indicative of survival in CRC. Moreover, we introduced red blood cell count (RBC) as an additional marker, despite limited research evidence, which has demonstrated its potential for predicting the long-term prognosis of hepatocellular carcinoma and cervical cancer [13,30]. However, its speci c role in prognostic assessment for CRC patients remains an area warranting further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we also evaluated other pertinent markers, including ALB, AGR, total protein, Hb, and BMI, which have previously been reported as indicative of survival in CRC. Moreover, we introduced red blood cell count (RBC) as an additional marker, despite limited research evidence, which has demonstrated its potential for predicting the long-term prognosis of hepatocellular carcinoma and cervical cancer [13,30]. However, its speci c role in prognostic assessment for CRC patients remains an area warranting further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of Hb to RDW (HRR) is a convenient prognostic marker for small cell lung cancer (SCLC), non-small cell lung cancer (NSCLC), and pulmonary large cell neuroendocrine carcinoma (PLCNEC) (Zhao et al, 2022). The combination of RDW, weight loss, and the metastatic lymph nodes were risk factors for the poor survival of patients with advanced oral cancer independent of other clinical and pathological characteristics (Trevisani et al, 2021) platelet-lymphocyte ratio > 184.9, and higher fasting glucose level, (Mota et al, 2022) the increased RDW-to-albumin ratio is independently associated with increased all-cause mortality in cancer patients (Lu et al, 2022).…”
Section: Cancersmentioning
confidence: 99%
“…The combination of RDW, weight loss, and the metastatic lymph nodes were risk factors for the poor survival of patients with advanced oral cancer independent of other clinical and pathological characteristics (Trevisani et al, 2021). Although shorter overall survival and disease‐free survival are associated with Hb ≤ 12.3 g/dL, hematocrit ≤ 38.5%, neutrophil–lymphocyte ratio > 2.9, platelet–lymphocyte ratio > 184.9, and higher fasting glucose level, (Mota et al, 2022) the increased RDW‐to‐albumin ratio is independently associated with increased all‐cause mortality in cancer patients (Lu et al, 2022).…”
Section: The Application Of Rdw In the Diagnosis Of Nonanemic Diseasesmentioning
confidence: 99%